Humidity influenced capacitance and resistance of an Al/DNA/Al Schottky diode irradiated by alpha particles - Al-Ta'ii, H.M.J.; Amin, Y.M.; Periasamy, V. (Nature Publishing Group, 2016)
Deoxyribonucleic acid or DNA based sensors, especially as humidity and alpha particle sensors have become quite popular in recent times due to flexible and highly optimizable nature of this fundamental biomaterial. Application of DNA electronics allow for more sensitive, accurate and effective sensors to be developed and fabricated. In this work, we examined the effect of different humidity conditions on the capacitive and resistive response of Aluminum (Al)/DNA/Al Schottky barrier structure when bombarded by time-dependent dosages of alpha particles. Based on current-voltage profiles, which demonstrated rectifying behaviours, Schottky diode parameters such as ideality factor, barrier height and series resistance was calculated. Results observed generally pointed towards a decrease in the resistance value from the pristine to the radiated structures. It was also demonstrated that under the effect of humidity, the capacitance of the DNA thin film increased from 0.05894 to 92.736 nF, with rising relative humidity level. We also observed the occurrence of the hypersensitivity phenomena after alpha irradiation between 2 to 4 min by observing a drop in the series resistance, crucial in the study of DNA damage and repair mechanisms. These observations may also suggest the exciting possibility of utilizing Al/DNA/Al Schottky diodes as potentially sensitive humidity sensors.